MENGGALI KONFLIK BATIN TOKOH TANIA PADA NOVEL “DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN” KARYA TERE LIYE UNTUK MENINGKATKAN MORALITAS - Duwi Rahayu Ningsih; Dianita Siti Lestari; Feby Rani Sokawati; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This article discusses the inner conflicts of the main character in a novel by Tere Liye entitled Fallen Leaves Never Hate the Wind. The aim of this research is to analyze the inner conflicts experienced by Tania, who is the main character, as well as the factors that cause the conflicts experienced. The method used in this research is descriptive qualitative. The approach used in this analysis is literary psychology. The results of this research show that people experience various types of inner conflict, namely love, anger, doubt, sadness and guilt. Each of these conflicts is triggered by situations experienced by the main character, such as the uncertainty of unrequited love and the loss of his mother. This research also found that Tania's inner conflict had a significant impact on her mental health, causing feelings of jealousy, deep sadness and anxiety. The conclusion of this research confirms that the inner conflict experienced by Tania reflects complex and universal emotional challenges. Tania's experience as the main character gives readers insight into the importance of understanding and accepting feelings in facing life's difficulties.